Self-Control in Responsibility Enhancement and Criminal Rehabilitation - Polaris Koi; Susanne Uusitalo; Jarno Tuominen (Springer, 2022)
Ethicists have for the past 20 years debated the possibility of using neurointerventions to improve intelligence and even moral capacities, and thereby create a safer society. Contributing to a recent debate concerning neurointerventions in criminal rehabilitation, Nicole Vincent and Elizabeth Shaw have separately discussed the possibility of responsibility enhancement. In their ethical analyses, enhancing a convict’s capacity responsibility may be permissible. Both Vincent and Shaw consider self-control to be one of the constituent mental capacities of capacity responsibility. In this paper, we critically examine the promise of improving convicts’ capacity responsibility by neuroenhancements of self-control to see whether the special characteristics of the inmate population make a difference in the analyses. As improving self-control by means of neurointerventions seems plausible, we then ask whether it is or could be a justified measure in court rulings. We conclude that, even if there are cases in which neurointerventions were warranted in the context of the stated goals of the criminal court, i.e., decreasing recidivism and rehabilitating the offenders to the society, due to the range of individual variability in the constitution of self-control, the prescription of specific neurointerventions of self-control falls outside the scope of legitimate court rulings.